English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

11p-6 = 3p+10

2007-10-08 10:28:49 · 22 answers · asked by Anonymous in Science & Mathematics Mathematics

22 answers

p=2

2007-10-08 16:31:44 · answer #1 · answered by ? 5 · 0 0

The goal with this type of problem is to isolate the variable "p" on one side of the equal sign and a real number on the other. The way to do this is to add, subtract, multiply or divide both sides of the equation by the same amounts to keep both sides of the equation balanced.

In this example, subtract "3p" from both sides: (11p-3p)-6=(3p-3p)+10. Doing the math leaves you with: 8p-6=10.

Then add 6 to both sides: 8p-6+6=10+6. Doing the math leaves you with: 8p=16.

Then divide both sides by 8: 8p/8=16/8. Doing the math leaves you with: p=2

To check your work, substitute 2 for "p" in the original equation 11p-6 = 3p+10: 11(2)-6=3(2)+10. Doing the math leaves you with 22-6=6+10 or 16=16. Since this result is true, then 2 is the correct solution for "p." (It's best to show your work this way to keep track of the steps you take to solve the equation.)

2007-10-08 17:57:30 · answer #2 · answered by Russ L 1 · 0 0

11p-6 = 3p+10 add 6 to both sides
11p = 3p + 16 subtract 3p from both sides
8p = 16 divide by 8 to solve for p
p = 2

understand the logic? For some people it is easier, if there is just one variable, to make it X. It sounds silly, but some people's minds work better like that because that is normally how they were tsught. Always remember to isolate your variable 1st. So the first question you should have asked yourself is: how do I get the P to one side of the eqation, and then go from there.

2007-10-08 17:33:59 · answer #3 · answered by Katie 3 · 0 0

First thing you need to do is get like terms.
11p-6 = 3p+10
-3p +6
Then subtract the 3p from the 11p and add the 10 and the 6
8p=16
Then divide the 16 by 8 to get the p on one side of the equal side.
Hope this helps!!!

2007-10-08 17:36:55 · answer #4 · answered by lgrant43110 1 · 0 0

11p-6= 3p+10
+6= +6 (seperate constants from variables)
11p=3p+16 (seperate constants from variables)
-3p -3p
7p=16 this is what you are left with.
divide by 7 to get p by its self
p=7/16

2007-10-08 17:33:51 · answer #5 · answered by bernel1403 5 · 0 0

11p-6 = 3p+10
11p-3p = 10+6
8p = 16
8p/8 = 16/8
p=2

You have to bring the numbers to one side and the unknows to the other. You know that when you move numbers or unknows over the equal sign their sign changes, keep tht in mind and solve for the unknown.

2007-10-08 17:34:48 · answer #6 · answered by zain k 2 · 0 0

you are looking for the value of p so:
1. put all the p's one one side and the rest to the other
11p-3p=10+6
2. combine like terms:
8p=16
3. solve for p by dividing both sides by 8
p=2
That's it. :)

2007-10-08 18:52:31 · answer #7 · answered by miriam_of_edinburgh 2 · 0 0

the answer is: p=2

make sure p is on one side of the equation and the other numbers are on the other

remember to change from + to - and - to + when crossing over the equals sign.

11p - 3p = 6 + 10
8p = 16
p = 2

2007-10-08 17:39:56 · answer #8 · answered by lazymonkey915 2 · 0 0

Watch carefully!

11p-6=3p+10
11p-3p=10+6
8p=16
p=16/8
p=2


11(2)-6=3(2)+10
22-6=6+10
16=16

The answer is p=2.

2007-10-08 17:37:43 · answer #9 · answered by pisces86 3 · 0 0

11p-6=3p+10

:11p-3p=10+6
:8p=16
:p=2

2007-10-08 17:31:57 · answer #10 · answered by az_2000 2 · 0 0

fedest.com, questions and answers